A simple unified stress-strain model for geotextile-wrapped soils. Issue 3 (June 2021) - Shen, Chaomin; Fan, Kewei; Liu, Sihong; Wang, Liujiang; Lai, Zhiqiang; Yuan, Weihai
Abstract: The stress-strain behaviour of geotextile-wrapped soils is a matter of great concern in geotechnical engineering practices. In this study, a unified stress-strain model for geotextile-wrapped soils is proposed and is applied to understand the strength and deformation characteristics of soilbags (woven bag-wrapped soils) in 2D biaxial loading. It is demonstrated that the strength of wrapped soils is greatly improved due to the wrapping effect, and the shearing contraction of the wrapped soils is more pronounced than that of the pure soils. The validity of the results is verified through numerical simulation using the discrete element method (DEM). The effect of the geometric size and material properties of the woven bag on the strength and deformation characteristics of the soilbags is also analyzed using the proposed model. The proposed model differs from existing phenomenological models in that it is able to predict the mechanical response of soilbags when the constitutive behaviours of the wrapped soils and the woven bag are given. Highlights: A unified stress-strain model for geotextile-wrapped soils is proposed. The strength and deformation characteristics of soilbags are studied using the proposed model. The effect of the size and properties of the bag on the strength and deformation characteristics of soilbags is analyzed.